2020
DOI: 10.1200/jgo.19.00109
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Aboriginal Peoples’ Cultural and Family Connections Can Help Inform the Development of Culturally Appropriate Cancer Survivorship Models of Care

Abstract: PURPOSE To explore the cancer diagnosis, treatment, and survivorship experiences of Aboriginal people in the Gippsland region, Victoria, Australia, and identify factors critical to the development of a culturally appropriate cancer survivorship model of care. PATIENTS AND METHODS Yarning circles were used to capture the stories of 15 people diagnosed with cancer and/or those of family members. Yarning circles were conducted in two locations in the Gippsland region. Sessions were facilitated by an Aboriginal El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 48 publications
2
61
0
Order By: Relevance
“…The scarcity of Indigenous staff and care providers, together with a high staff turnover and variable access to language translation services, exacerbated the cultural disconnect between Indigenous patients and CTS-NT. Similar concerns have been identified for Indigenous cancer patients in Queensland [ 30 ], Western Australia [ 15 ] and Victoria [ 31 ]. Marcusson-Rababi et al found that Indigenous women undergoing gynaecological cancer treatment in Queensland experienced a similar range of difficulties impacting their experience of cancer care, including: unsympathetic delivery of bad news, confusing terminology, language difference, and a lack of available interpreters [ 30 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The scarcity of Indigenous staff and care providers, together with a high staff turnover and variable access to language translation services, exacerbated the cultural disconnect between Indigenous patients and CTS-NT. Similar concerns have been identified for Indigenous cancer patients in Queensland [ 30 ], Western Australia [ 15 ] and Victoria [ 31 ]. Marcusson-Rababi et al found that Indigenous women undergoing gynaecological cancer treatment in Queensland experienced a similar range of difficulties impacting their experience of cancer care, including: unsympathetic delivery of bad news, confusing terminology, language difference, and a lack of available interpreters [ 30 ].…”
Section: Discussionsupporting
confidence: 63%
“…Shahid et al found that that providers commonly lacked an understanding of Aboriginal culture, and the socioeconomic conditions and life circumstances of Aboriginal families [ 15 ]. Ristevski et al found that cancer care providers in Victoria has little understanding of the importance of cultural and family connections to Indigenous Australians undergoing cancer treatment [ 31 ]. The importance of having Indigenous health care providers working with Indigenous cancer patients has been identified in numerous studies [ 6 , 15 , 28 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noting that "most health research is relevant for Indigenous peoples, and most researchers are non-Indigenous," 15 the authors caution that, "if researchers don't engage with Indigenous research principles, health research can and does result in significant harm for Indigenous peoples." 15(p1) An impressive example of research underpinned by the principles outlined by this caution is the article by Ristevski et al, 16 who present a deep analysis of the importance of Aboriginal peoples' cultural and family connections to inform the development of culturally safe cancer survivorship models of care. Data were collected through yarning, a culturally appropriate methodology relevant to Indigenous Australians when sharing information, knowledge, and culture.…”
Section: Indigenous Empowermentmentioning
confidence: 99%
“…15 Ristevski et al found that cancer care providers in Victoria has little understanding of the importance of cultural and family connections to Indigenous Australians undergoing cancer treatment. 31 The importance of having Indigenous health care providers working with Indigenous cancer patients has been identi ed in numerous studies. 6,15,28,32 The value of ILOs in supporting Indigenous Australians with chronic illness has been reported in cardiovascular care.…”
Section: Information and Communicationmentioning
confidence: 99%